Tropical cyclone activity over the Southwest Tropical Indian Ocean. Issue 8 (27th August 2016) - Burns, Jessica M.; Subrahmanyam, Bulusu; Nyadjro, Ebenezer S.; Murty, V. S. N.
Abstract: The Southwest Tropical Indian Ocean (SWTIO) is a key region for air‐sea interaction. Tropical cyclones (TCs) regularly form over the SWTIO and subsurface ocean variability influences the cyclogenesis of this region. Tropical cyclone days for this region span from November through April, and peak in January and February during austral summer. Past research provides evidence for more tropical cyclone days over the SWTIO during austral summer (December–June) with a deep thermocline ridge than in austral summer with a shallow thermocline ridge. We have analyzed the Argo temperature data and HYbrid Coordinate Ocean Model (HYCOM) outputs while focusing on the austral summer of 2012/2013 (a positive Indian Ocean Dipole (IOD) year and neutral El Niño Southern Oscillation (ENSO) year) when seven named tropical cyclones developed over the SWTIO region. This study reveals that the climatic events like the IOD and ENSO influence the cyclonic activity and number of TC days over the SWTIO. We ascertain that the IOD events have linkages with the Barrier Layer Thickness (BLT) in the SWTIO region through propagating Rossby waves, and further show that the BLT variability influences the cyclonic activity in this region. Key Points: Positive IOD event in 2012 influenced the number of TC days through downwelling Rossby waves 4–5 month lag correlation between Dipole Mode Index and number of TC days in the SWTIO Negative correlation between Oceanic Niño Index of positive ENSO phase and TC activity in the SWTIO